Avaliação ambiental e de bem-estar da criação de suínos em sistemas de cama sobreposta e convencional - Amaral, Pedro Ivo Sodré (2016)
The objective of this work was to evaluate the environmental and welfare aspects of installations for pigs. The study was conducted at the IFET – Southeastern Minas Gerais, Brazil, Rio Pomba/MG campus. We used three stalls in an installation for producing finishing pigs, consisting of wood shavings bedding (MAR), rice husk bedding (CSA) and conventional system with concrete floors (CON) and water blade. Data of air temperature (TBS), relative air moisture (UR) and globe temperature were collected, and the BGHI (black globe and humidity index) was calculated. For the aerial environment, we measured the concentrations of NH3 and CO 2 in the air mass at 08, 10, 14 and 16 hours. In the same manner, we measured floor, surface and depth (20 cm below the surface) temperatures. The physiological parameters observed were respiratory frequency (FR), skin temperature (TP) and rectal temperature (TR), at 08, 10, 14 and 16 hours. The behavior of the piglets was observed from 08 to 17h30m, every 10 minutes. The behavior were recorded according to an ethogram with previously defined patterns, in addition to activity index (IA%). Every 30 minutes we verified the spatial distribution of the pigs, which remained lying (IO%). The data for NH3 and CO 2 concentration, surface and depth temperatures, in addition to Stall Occupation Index (IO%) were collected from points spaced within the stalls, totalizing nine locations. The means for BGHI were lower for treatments in bed. There was no difference for TBS. However, the mean for UR was lower for MAR. The concentration of NH3 was superior in the CON system (4 ppm) in relation to the other systems (2 ppm for CSA and MAR). The data for surface and depth temperatures were higher for CSA (P<0.01). The results of the physiological parameters showed that the FR of the animals housed in the systems with overlapping beds was superior to the conventional system. There were no differences for TP or TR. Regarding the behavior, there only occurred difference for the ―drinking‖ pattern, superior for MAR, and ―eating‖ superior for CON. The results for IA% revealed higher frequencies for CSA in relation to CON. Higher accumulation of NH3 was verified in the bathroom areas, in all systems evaluated. For the CO 2, the point of greater gas accumulation occurred due to the concentration of animals and to the lower air renewal rate. Given this diagnosis, we can infer that t he system of overlapping bed offers adequate conditions to the finishing piglet and, among the bedding materials evaluated, the CSA is predominant.